Kikiskawâwasow - prenatal healthcare provider perceptions of effective care for First Nations women: an ethnographic community-based participatory research study. Issue 1 (December 2016) - Oster, Richard; Bruno, Grant; Montour, Margaret; Roasting, Matilda; Lightning, Rick; Rain, Patricia; Graham, Bonny; Mayan, Maria; Toth, Ellen; Bell, Rhonda
Abstract Background Pregnant Indigenous women suffer a disproportionate burden of risk and adverse outcomes relative to non-Indigenous women. Although there has been a call for improved prenatal care, examples are scarce. Therefore, we explored the characteristics of effective care with First Nations women from the perspective of prenatal healthcare providers (HCPs). Methods We conducted an ethnographic community-based participatory research study in collaboration with a large Cree First Nations community in Alberta, Canada. We carried out semi-structured interviews with 12 prenatal healthcare providers (HCPs) that were recorded, transcribed, and subjected to qualitative content analysis. Results According to the participants, relationships and trust, cultural understanding, and context-specific care were key features of effective prenatal care and challenge the typical healthcare model. HCPs that are able to foster sincere, non-judgmental, and enjoyable interactions with patients may be more effective in treating pregnant First Nations women, and better able to express empathy and understanding. Ongoing HCP cultural understanding specific to the community served is crucial to trusting relationships, and arises from real experiences and learning from patients over and above relying only on formal cultural sensitivity training. Consequently, HCPs report being better able to adapt a more flexible, all-inclusive, and accessible approach that meets specific needs of patients. Conclusions Aligned with the recommendations of the Truth and Reconciliation Commission of Canada, improving prenatal care for First Nations women needs to allow for genuine relationship building with patients, with enhanced and authentic cultural understanding by HCPs, and care approaches tailored to women's needs, culture, and context.